A low‐profile dual‐polarized patch antenna array based on quasi‐cruciform coupling slot. Issue 2 (13th November 2021) - Liao, Dunwei
Abstract: A dual‐polarized microstrip patch antenna array is designed, constructed, and measured. The patch array is compactly arranged through the design of a suitable series–parallel hybrid feed network. The antenna array demonstrates the bandwidth (10 dB return loss) of port 1 and port 2 are 13.8% (5.41–6.21 GHz) and 9.7% (5.5–6.06 GHz) in measured results respectively. The antenna maintains −27 dB cross‐polarization level in the operating band, whereas the isolation for the two orthogonal ports is 39 dB and more. In addition, the antenna array prototype achieves average gains of 13.5 dBi for horizontal and 13.9 dBi for vertical polarizations, respectively. Moreover, the profile of the array is very low based on the proposed antenna unit with a low profile of 3.1 mm (0.06 λ0 at 5.8 GHz), which is a microstrip‐fed dual‐polarized antenna.